Stochastic control approach to the multi-armed bandit problems - Treetanthiploet, T (2021)
A multi-armed bandit is the simplest problem to study learning under uncertainty when decisions affect information. A standard approach to the multi-armed bandit often gives a heuristic construction of an algorithm and proves its regret bound. Following a constructive approach, it is often possible to find a scenario where following heuristic approaches gives a poor decision.